CULTURE AND TOURISM OF BANTEN IN A COLLECTION OF SHORT STORIES “BANTEN: SUATU KETIKA” - Vedia Vedia; Fachria Marasabessy (Himpunan Sarjana-Kesusastraan Indonesia (HISKI), 2020)
This research analyzes a collection of short stories entitled “Banten; Suatu Ketika” by using the sociology of literature and tourism approach. The sociology of literature approach is used in order to see the culture contained in the short story. While tourism is used to see the extent to which this short story is able to lift tourism in the Banten region. The research shows that the collection of short stories “Banten; Suatu Ketika” has a rich cultural value and promotes tourism sites in Banten area. The culture of Banten reflected is not only limited to how the people of Banten live but also contains several myths that are believed to be the culture itself. The setting of the place as well as the various types of typical foods of Banten used in the collection of short stories magically are able to provide tourism information in the Banten region.